NPC1 Deficiency Contributes to Autophagy-Dependent Ferritinophagy in HEI-OC1 Auditory Cells - Liang, Lihong; Wang, Hongshun; Yao, Jun; Wei, Qinjun; Lu, Yajie; Wang, Tianming; Cao, Xin (Frontiers in Molecular Biosciences, 2022)
Niemann–Pick type C disease (NPCD) is a rare genetic syndrome characterized by cholesterol accumulation in multiple organelles. NPCD is mainly caused by gene deficiency of NPC intracellular cholesterol transporter 1 (NPC1). It has been reported that some of the NPCD patients exhibit clinical features of progressive hearing loss at high frequency and iron disorder, but the underlying relationship is unknown. A recent study has reported that ferroptosis contributes to the impairment of cochlear hair cells that are related to sensory hearing. In this study, we generated NPC1-deficient HEI-OC1 cells to show the effect of NPC1 deficiency on cochlear outer hair cells. We found that NPC1 deficiency enhances autophagy-dependent ferritinophagy to release Fe (II). Our work provides important insights into the effect of NPC1 deficiency in auditory cells, indicating that it induces ferroptosis and results in hearing loss.